PENERAPAN EFEKTIVITAS e-GOVERNMENT KECAMATAN KALIORANG KABUPATEN KUTAI TIMUR - e-Government Implementation Kaliorang District of East Kutai Regency - Hadijah, Siti (PREDIKSI, 2016)
e-Government is a system Subdistrictapplicationwhich canused for transaction processing and monitoring the creation of documents that exist in the government district of e-Government Sub-district is one of the application services of the program Smart City declared by bupat i and Vice Regent of East Kutai Regency is an effort of the government in developing a system of effective governance, efficient and transparent by optimizing the use of Information Technology systems.e-Government Sub-district is now implemented by 6 Kaliorang village in the district of East Kutai Regency, one of which the District Kaliorang.Then the unit of analysis in the present study the implementation of E-Government Kaliorang District of East Kutai.This type of research used by the authors in this research is descriptive qualitative. Data collection technique were interview, observation and documents related to the study.Data analysis techniques in the study conducted qualitatively.The results of this study explained that the implementation of e-Government Kaliorang District of East Kutai Regency was quite effective.It is measured based on indicators measuring the effectiveness byGibson.